Entrepreneurship in the era of society 5.0: Navigating digitalization for innovation and growth - Putra, Juniawan Mandala; Karundeng, Deby R.; Gofur, Abdul; Tresnadjaja, Reynaldi; Suhara, Ade; Sukmayadi, Sukmayadi; Sopyan, Ahmad (Goodwood Publishing, 2024)
Purpose: This study examines the relationship between entrepreneurship and digitalization in Society 5.0, highlighting how entrepreneurs can leverage digital technologies for innovation and economic growth. Research Methodology: This study used a quantitative approach with 200 Indonesian entrepreneurs utilizing digital technology. Data were collected via an online questionnaire and analyzed using SEM-PLS in Smart PLS to explore digitalization’s impact on innovation and growth. Results: The findings show that digital technologies such as AI, the Internet of Things, and big data help entrepreneurs innovate products, improve efficiency, and expand markets. These technologies provide global market access, enhance customer experience, and increase business sustainability, making entrepreneurs more competitive and adaptable. Conclusions: Entrepreneurs in Society 5.0 must adopt digitalization for business growth, overcoming challenges like technology dependence, security risks, and skill gaps. Collaboration between the government, private sector, and educational institutions is key to addressing these obstacles. Limitations: The study’s limitations include reliance on self-reported data, regional focus, and exclusion of other entrepreneurial factors such as social and environmental impact. Future research could address these gaps by exploring broader contexts and variables in the study. Contributions: This research contributes to the development of digital policies, enhances the understanding of entrepreneurship in Society 5.0, and provides strategies for leveraging digital technologies in business innovation and growth.